(untitled) (Lancaster, 1999)
The first single volume reference on the use of genetic engineering and molecular biology for plant food production, this book provides basic to in-depth approaches at the molecular level combining agricultural technology with food science and technology. It focuses on biotechnology 's role in the manipulation of cell and plant growth for enhanced productivities. Includes over 2100 key literature references.
Keywords: Plant biotechnology,Công nghệ sinh học thực vật